Melody of Health: The Correlation of Music Therapy on the Mental Health of Students at UIN Syarif Hidayatullah Jakarta - Jannah, Angel Cahya Raudhatul (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
Mental health is a crucial aspect of individual life, encompassing psychological balance, the ability to cope with pressure, and contributions to the community. The increasing prevalence of mental health disorders, particularly among university students, necessitates effective stress management strategies, one of which is music therapy. This study aims to analyze the relationship between music preferences and the mental health of students in the Islamic Guidance and Counseling program at UIN Syarif Hidayatullah Jakarta using a quantitative approach with a descriptive correlational design. A total of 52 students were selected using the snowball sampling technique, and data were collected through questionnaires measuring stress levels, anxiety, and music preferences. The results indicate that the majority of students experience stress due to academic and social pressures; however, listening to music, particularly calming and uplifting genres, can significantly reduce stress and anxiety while enhancing mental well-being. The findings confirm that music can be an effective strategy for managing student stress, and educational institutions may consider integrating music into student wellness programs.